Dusky Dolphin Trophic Ecology: Their Role in the Food Web - Dans, Silvana Laura; Crespo, Enrique Alberto; Koen Alonso, Mariano; Markowitz, Tim M.; Beron Vera, Barbara; Dahood, Adrián D.
Like most top predators, dusky dolphins (Lagenorhynchus obscurus) may play different roles in marine ecosystems, although they are still poorly known. Dusky dolphins are an integral part of several marine ecosystems of the southern hemisphere. Among other cetaceans, pinnipeds, seabirds, and sharks, dusky dolphins represent the near-terminal links in the food webs in which they are embedded. This set of species is also referred to as the “top predators” or “upper trophic level predators” and the study of the trophic role dusky dolphins play in marine ecosystems is driven mostly by the same interests that one has in top predators. The goal of this chapter is to briefly summarize what is known about their trophic ecology and to attempt to develop, within the limitations of the available data, an initial description of the trophic role of dusky dolphins in their ecosystems. To achieve this goal, several topics are presented, including diet and feeding habits, relationships with other top predators, competition and kleptoparasitism, the role in the transmission of parasites, and finally their trophic relationships with fisheries. Fil: Dans, Silvana Laura. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina Fil: Crespo, Enrique Alberto. Universidad Nacional de la Patagonia "San Juan Bosco"; Argentina Fil: Koen Alonso, Mariano. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Fisheries And Ocean Canada. Northwest Atlantic Fisheries Centre; Canadá Fil: Markowitz, Tim M. University of Canterbury; Nueva Zelanda Fil: Beron Vera, Barbara. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina Fil: Dahood, Adrián D. Texas A&M University; Estados Unidos